2016
DOI: 10.1016/j.cherd.2016.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Selective agglomeration of fine coal using a water-in-oil emulsion

Abstract: Fine coal may be separated from an aqueous suspension of coal and mineral particles through the application of a pure oil. The pure oil preferentially wets and agglomerates only the coal, forming a high quality, granular product. However, the use of the pure oil also comes at a relatively high cost and this cost prohibits commercial implementation of this process. In this work a new, economic binder, was introduced. This binder consisted of a high internal phase water-in-oil emulsion which was 95 vol% water an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 14 publications
2
24
0
2
Order By: Relevance
“…In saying that, however, this potential reduction is highly dependent upon the emulsion acting to agglomerate the fine coal in the same manner as pure oil. This is not an unreasonable proposition and early indications have shown that a HIP emulsion can agglomerate fine coal in a similar manner to pure oil [18]. However, some significant differences between the two binders were noted as a result of this work.…”
Section: Introductionmentioning
confidence: 82%
“…In saying that, however, this potential reduction is highly dependent upon the emulsion acting to agglomerate the fine coal in the same manner as pure oil. This is not an unreasonable proposition and early indications have shown that a HIP emulsion can agglomerate fine coal in a similar manner to pure oil [18]. However, some significant differences between the two binders were noted as a result of this work.…”
Section: Introductionmentioning
confidence: 82%
“…Approach (ii)-increasing the apparent size of particles-includes shear flocculation [12], carrier flotation [13,14], polymer flocculation [15][16][17] and oil agglomeration [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…All of these techniques have their own benefits and drawbacks, but from the perspective of economics, oil agglomeration-a method to increase particle size using oil as a bridging liquid under intense mixing-is the most promising because oil is relatively inexpensive, the process could be easily integrated into existing flotation circuits, and the technique could effectively improve the recovery of fine particles. Utilization of emulsified oil for agglomeration-flotation could reduce the amount of oil [20][21][22]. This method has been mainly studied in coal flotation [19] and some sulfide minerals such as molybdenite [23], sphalerite and galena [24].…”
Section: Introductionmentioning
confidence: 99%
“…In other recent work, van Netten and co-workers have developed a novel hydrophobic binder for use in selective agglomeration. Originally developed with the aim of reducing the oil required in the selective agglomeration process, the hydrophobic binder has been shown to achieve rapid recovery across the full fine particle size range (van Netten et al, 2013 , 2014 , 2015 , 2016 ). A high internal-phase (HIP) water in oil emulsion is used as the binder.…”
Section: Introductionmentioning
confidence: 99%
“…Early work using the HIP water in oil emulsion binder showed a 2–3-fold (van Netten et al, 2013 ), followed by a 7-fold (van Netten et al, 2014 ) reduction in organic liquid requirements compared to conventional oil agglomeration in the recovery of coal particles. The most recent development however, resulted in a 10-fold reduction (van Netten et al, 2016 ). The hydrophobic emulsion binder consisted of a 95% dispersed aqueous phase and a 5% continuous organic phase.…”
Section: Introductionmentioning
confidence: 99%